2019
DOI: 10.1021/acs.jmedchem.9b00533
|View full text |Cite
|
Sign up to set email alerts
|

Identification of 2-Imidazopyridine and 2-Aminopyridone Purinones as Potent Pan-Janus Kinase (JAK) Inhibitors for the Inhaled Treatment of Respiratory Diseases

Abstract: Janus kinases (JAKs) have a key role in regulating the expression and function of relevant inflammatory cytokines involved in asthma and chronic obstructive pulmonary disease. Herein are described the design, synthesis, and pharmacological evaluation of a series of novel purinone JAK inhibitors with profiles suitable for inhaled administration. Replacement of the imidazopyridine hinge binding motif present in the initial compounds of this series with a pyridone ring resulted in the mitigation of cell cytotoxic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 30 publications
0
11
0
Order By: Relevance
“…Promising clinical results with Nemiralisib (GSK2269557), a PI3Kδ isoform-selective inhibitor, support the efficacy of the inhaled route of delivery [36 • ]. Bach et al have identified potent pan-JAK inhibitors that show good retention in the lung following intra-tracheal administration [62]. Importantly, these compounds reduced LPS-induced lung inflammation in a mouse model and had poor oral bioavailability suggesting reduced unwanted systemic effects [62].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Promising clinical results with Nemiralisib (GSK2269557), a PI3Kδ isoform-selective inhibitor, support the efficacy of the inhaled route of delivery [36 • ]. Bach et al have identified potent pan-JAK inhibitors that show good retention in the lung following intra-tracheal administration [62]. Importantly, these compounds reduced LPS-induced lung inflammation in a mouse model and had poor oral bioavailability suggesting reduced unwanted systemic effects [62].…”
Section: Discussionmentioning
confidence: 99%
“…Bach et al have identified potent pan-JAK inhibitors that show good retention in the lung following intra-tracheal administration [62]. Importantly, these compounds reduced LPS-induced lung inflammation in a mouse model and had poor oral bioavailability suggesting reduced unwanted systemic effects [62].…”
Section: Discussionmentioning
confidence: 99%
“…For example, tofacitinib and ruxolitinib lack subtype selectivity, affecting JAK1/JAK2/JAK3/TYK and JAK1/JAK2, respectively, which results in dose-limiting side effects, such as JAK2 inhibition-driven cytopenias . Recently, novel purinone pan-JAK inhibitors were identified, which have potential for treatment of respiratory diseases via the inhalation route . The best compound demonstrated good selectivity for the JAK family.…”
Section: Successful Kinase Inhibitors For Nononcologic Diseasesmentioning
confidence: 99%
“…The value of this group of compounds can be demonstrated by their utilization as a reagent in the synthesis of biologically active compounds over the years. [14][15][16][17][18][19][20] For instance, they have been used in rational drug design of topically administered caspase 1 inhibitors for the treatment of inflammatory acne, 14 in the synthesis and biological evaluation of pyrimidine derivatives as novel human Pin1 inhibitors in the cancer treatment, 15 and the preparation of scaffolds for the design of Rac1−Tiam1 protein−protein interaction inhibitors 16,17 . Title compounds were also employed in the synthesis of alkaloid meridianin G, 18 and the synthesis of the insect feeding deterrent peramine.…”
Section: Introductionmentioning
confidence: 99%
“…19 In the most recent article, they are utilized in the synthesis of 2-imidazopyridine and 2-aminopyridone purinones as potent Pan-Janus kinase (JAK) inhibitors for the inhaled treatment of respiratory diseases. 20…”
Section: Introductionmentioning
confidence: 99%